MAGI1 inhibits interferon signaling to promote influenza A infection - Wang, Yin; Abe, Jun-ichi; Chau, Khanh M.; Wang, Yongxing; Vu, Hang Thi; Reddy Velatooru, Loka; Gulraiz, Fahad; Imanishi, Masaki; Samanthapudi, Venkata S. K.; Nguyen, Minh T. H.; Ko, Kyung Ae; Lee, Ling-Ling; et al. (Frontiers in Cardiovascular Medicine, 2022)
When influenza virus infects cells, it changes cellular metabolism in such a way that allows virus particles to replicate efficiently. This metabolic engineering takes place soon after virus infects cells, for which the PSD95/DiscLarge/ZO-1 (PDZ) domain of certain proteins is known to play a role. Membrane-associated guanylate kinase with inverted domain structure-1 (MAGI1) is a scaffold protein with 6 PDZ domains, and we have shown that it is involved in the regulation of endothelial cell (EC) activation and development of atherosclerosis in mice. Since recent studies indicate that the vascular endothelium can be infected by influenza A virus (IAV) and plays a role in the pathogenesis of influenza, we investigated the role of MAGI1 in IAV infection using cultured human umbilical vein endothelial cells (HUVECs) as well as human lung microvascular endothelial cells (HULECs). We found increased MAGI1 mRNA expression in IAV-infected cells. Conversely, when MAGI1 depleted ECs were infected with IAV, virus infection and replication was greatly suppressed. Our microarray studies revealed that depletion of MAGI1 in HUVECs increased the protein expression and signaling networks involved in interferon production. Specifically, we found that the MAGI1 null condition induced expression of anti-viral response genes including interferon-induced GTP-binding protein MX1, an antiviral protein, interferon beta1, a cytokine promotor STAT1 (signal transducer and activator of transcription 1), and also increased protein expression levels of STAT1, phosphorylated STAT5 and MX1. Co-transfection of HUVECs with siMX1 and siMAGI1 impaired MAGI1 depletion-induced suppression of IAV infection. When lung ECs isolated from mice that express unactivatable MX1 were treated with MAGI1 siRNA, IAV replication was not inhibited in these cells. Furthermore, we found nuclear localization of interferon regulatory factor 3 (IRF3) in MAGI1 depleted cells, indicating that MAGI1 depletion elicits the interferon production and signaling. Taken together, we conclude that IAV infection and replication occurs in ECs in a MAGI1 expression dependent manner. Thus, MGAI1 depletion in ECs suppresses IAV replication, and this suppression is due to increased MX1 expression, which induces IRF3 activation and interferon production. MAGI1 can be a potential therapeutic target for influenza.